Effect Of Nisin On Oxidative Stability And Microbial Quality Of Almond- And Walnut-Enriched Chevon Nuggets (Applied Biological Research, 2016)
A study was undertaken to assess the efficacy of nisin on oxidative  stability and microbial quality of chevon nuggets supplemented with  almond and walnut at 5 and 10% level, respectively. Chevon nuggets  ere aerobically packaged in low density polyethylene (LDPE) pouches  along with control and evaluated for storage quality for 21 days under  refrigerated conditions (4±1oC). The products were analyzed for various  physico-chemical, microbial and sensory parameters. The study revealed  that with increase in storage period the free fatty acid (FFA) content, thiobarbituric acid reactive substances (TBARS), total plate count and  psychrophillic count showed significant increase; whereas sensory  parameters showed significant decrease. Nisin treated preparations had  significantly low TBARS and FFA values than non-nisin treated  preparations. Nisin-treated preparations had significantly low total  plate- and psychrotropic-counts. The nisin treated products were  successfully stored for 14 days under refrigeratedconditions (4±1oC) in  LDPE pouches and the product showed better acceptability.
Keywords: Almond; chevon; nisin; nuggets; refrigerated storage; walnut